Genetic diversity and verbascoside content in natural populations of Pyrostegia venusta (Ker Gawl.) Miers - Gavilan, Natália Helena [UNESP]; Morel, Lucas Junqueira de Freitas; Coppede, Juliana da Silva; Taleb-Contini, Silvia Helena; França, Suzelei de Castro; Bertoni, Bianca Waléria; Pereira, Ana Maria Soares (Springer Nature, 2022)
Background: Pyrostegia venusta (Ker Gawl.) Miers occurs in threatened biodiversity hotspots of Cerrado and Atlantic forest biomes in Brazil and is used in traditional medicine to treat various respiratory and skin diseases. Methods and results: This study (i) examined the genetic diversity and structure of six natural populations of P. venusta from different Brazilian regions using sequence-related amplified polymorphism (SRAP) markers; and (ii) compared the intra- and inter-populational levels of the bioactive component verbascoside using high-performance liquid chromatography. The population from Nova Mutum, Mato Grosso, presented the highest genetic variability (Nei index H = 0.2759; Shannon index I = 0.4170; 85.14% polymorphic loci), whereas the population from Araxá, Minas Gerais, presented the lowest genetic variability (H = 0.1811; I = 0.2820; 70.27% polymorphic loci). The intra-populational variability (79%) was significantly higher (p = 0.001) than the inter-populational variability (21%). The populations were clustered into two groups but their genetic differentiation was not associated with geographical origin (Mantel test, r = 0.328; p > 0.05). The verbascoside content significantly differed (p > 0.05) among the six populations and between the individuals from each population. The highest verbascoside levels (> 200 µg/mg extract) were detected in populations from Araxá and Serrana, while the lowest verbacoside levels were detected in populations from Paranaíta and Sinop. Conclusions: This is the first report on the use of SRAP markers to analyze genetic variability in the family Bignoniaceae. Our findings shall help to better understand the genetic and chemical diversity of P. venusta populations, as well as provide useful information to select the most appropriate individuals to prepare phytomedicines.
Keywords: Bignoniaceae; Flame-flower; Pyrostegia venusta; SRAP analysis; Verbascoside levels